Metal-free, radical 1,6-conjugated addition of cyclic ethers with para-quinone methides (p-QMs) - More, Satish G.; Suryavanshi, Gurunath (Organic & Biomolecular Chemistry, 2019)
An efficient method for metal-free C-C bond formation between p-quinone methides (p-QMs) and cyclic ethers via a radical pathway to afford substituted diarylmethanes and triarylmethanes or to effect the -alkylation of the cyclic ethers has been developed. Also, the synthesis of 3,3-disubstituted oxindoles with stereogenic quaternary carbon centers was successfully achieved under mild reaction conditions.